Solusi Etis Bagi Pengelolaan Keuangan Berbasis Nilai Islam - Tassya Putri Azzahra; Rayyan Firdaus (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
In writing this article, the author examines the role of the laity in the church, highlighting the development of their participation methods over time. The laity, as non-clergy members, contributed to the mission of the church and the spread of the gospel. From an active role in the early church, they experienced a transformation in the middle ages, but the protestant reformation restored their involvement through the concept of the "priesthood of all believers." the research method used is a literature study with qualitative analysis of relevant documents and literature. This study shows that the laity are not only recipients of teachings, but also agents of significant change in life